Body Weight and Measurements of Akbas Dogs in Its Nature Work Condition - Atasoy, Fatih; Ugurlu, Mustafa; Ozarslan, Bora; Yakan, Akin (Ankara Univ Press, 2011)
This study was carried out to determine body weight, some body and head measurements in different age and sex groups of Akbas dogs. The least squares means of body weights were found to be 41.66, 40.44 and 44.00 for Eskisehir, Sivrihisar and Golbasi regions; 40.05, 40.88, 43.20 and 43.06 for 1, 2, 3, 4 years of age and 43.78, 39.77 kg for male and female dogs respectively. Least squares means of wither heights were determined as 64.61, 64.20 and 64.46cm for regions, 63.37, 64.63, 64.74 and 64.75 cm for age groups; 66.36 and 62.30 cm for male and female groups respectively. These data were 64.47, 66.34, 67.38; 63.50, 67.44, 66.31, 66.84; 67.19, 64.98 cm for body lengths; 26.00, 26.34, 28.01, 24.93, 27.14, 27.94, 26.96; 27.34, 26.26cm for chest depths; 20.43, 20.41, 21.04; 18.85, 20.68, 21.86, 20.85; 20.89, 20.36 cm for chest widths; 82.63, 80.17, 82.66; 78.37, 81.86, 83.82, 83.67; 82.62, 80.41cm for hearth girths; 12.99, 13.25, 14.02; 13.37, 13.31, 13.56, 13.50; 13.91, 12.92 cm for front cannon bone circumference and 12.14, 12.26, 12,69; 12.20, 12.47, 12.54, 12,27; 12.72, 12.00 cm for hind cannon bone circumference respectively. The least squares means were 27.77, 27.36, 31.01; 27.77, 29.20, 28.78, 29.10; 29.43, 28.02 cm for head length; 10.74, 11.49, 14.17; 11.90, 12.98, 11.84, 12.02; 11.96, 12.45cm for muzzle length; 16.31, 15.82, 16.44; 15.07, 16.33, 16.54, 16.62; 16.71; 15,62cm for cars interval and 5.76, 5.64, 7.03; 6.08, 6.30, 6.15, 6.08; 6.26, 6.05cm for eyes interval respectively. The effects of region and sex on body weight, some body and head measurements were found statistically significant. In conclusion a small variation in body and head measurement was observed among regions. This circumferences put out the importance of protect and proliferation of this genetic sours in its nature regions Sivrihisar. The profile of this dog was found to be square that make it different with Kangals. On the contrary with the classic knowledge's only one Akbas dogs with the long coat was observed in this research that coming out the importance of put it under protection urgently.
Keywords: Akbas Dog; Body Measurements; Head Measurements; Live Weight